EFFECT OF CALCIUM CHANNEL BLOCKERS ON HEART FAILURE: A SYSTEMATIC REVIEW AND NETWORK META-ANALYSIS. (June 2022) - Alsanosi, Safaa; Roos, Nur Aishah Binti Che; Alsieni, Mohammed; Lip, Stefanie; Mccallum, Linsay; Shahzad, Naiyer; Padmanabhan, Sandosh
Abstract : Objective: Hypertension is a major risk factor for heart failure (HF). Antihypertensive therapy, in general, has a protective effect on incident HF with diuretics, ACEI, and ARBs particularly effective. Previous systematic reviews have produced inconsistent results about the effect of CCBs on HF. We conducted a systematic review and network meta-analysis to evaluate patients with hypertension treated with CCBs and incident HF. Design and method: Publications of head-to-head andomised controlled trials (RCTs) of CCBs were retrieved from MEDLINE, EMBASE, Web of Science, and Cochrane (January 2000- August 2021). We included RCTs with at least 100 participants and with a minimum follow-up of one year. Two authors independently selected the included trials, evaluated the risk of bias, and retrieved the data on HF. Fixed effect meta-analyses were performed to summarise the pooled risk ratios (RRs) of HF between treatment arms followed by network meta-analyses incorporating direct and indirect data. Results: The initial literature search identified 4740 records. After duplicates were excluded, there were 2602 records. Totally, 652 RCTs were excluded after a full-text review of the 674 eligible studies. In the end, 22 RCTs with a total of 164, 834 participants were included in our meta-analysis. As to the effect of CCBs on HF, ACEIs, ARBs, DIs, and BBs are all superior to CCBs in the prevention of HF. In comparison to the placebo, the point estimate for CCB was less than 1 but it did not reach statistical significance in the overall analysis, but it attained statistical significance in the sensitivity analysis. (The pooled RR in the fixed effect model was 0.74 [95% CI: 0.59, 0.92; I2 = 22%; X2 p = 0.007]). The relative risk of HF compared with CCB was 0·88 [0 8–0·97] for ACEI, 0·84 [0 75–0·95] for ARB, 0·87 [0 77–0·98] for BB, 0·75 [0 69–0·82] and 1.11 [0 94–1.32] for placebo. Conclusions: The findings of our systematic review and meta-analysis do not support the hypothesis that CCBs are effective in the prevention of HF. However, to gain a greater understanding of the potential effect of CCBs, further clinical studies and meta-analyses are needed to pool study results and strengthen statistical validity.